Unilateral, frontal polymicrogyria and supratentorial white matter microcysts in fetus with Joubert syndrome and related disorders: Prenatal diagnosis with magnetic resonance imaging - Koprivšek Katarina; Bjelan Mladen; Lučić Miloš; Kostić Dejan; Šveljo Olivera; Kozić Duško (Vojnosanitetski Pregled)
Introduction. Joubert syndrome (JS) and related disorders (JSRD) are a group of rare multiple congenital anomalies syndromes, defined by complex midbrain-hindbrain malformation that creates the “molar tooth sign” (MTS) on brain imaging and may be associated with multisystem organ pathology, mainly of the retina, kidney, liver and skeleton. Prenatal diagnosis of JSRD has proved difficult because of the rarity of the condition and low sensitivity of ultrasound in evaluation of the fetal posterior fossa (PF) in most affected fetuses. Case report. We presented an unusual case of JSRD, pure Joubert syndrome with unilateral frontal polymicrogyria and supratentorial white matter microcysts, diagnosed by magnetic resonance imaging (MRI), in fetus aged 30 gestational weeks. The distinctive MRI features of this rare ciliopathy were confirmed by 6-months postnatal MRI study. The postnatal outcome was poor; clinical follow- up in the first 6 months of life confirmed hypotonia, developmental delay, oculomotor apraxia and seizures. Conclusion. To the best of our knowledge, fetal MRI features of the coexistence of pure JS and supratentorial abnormalities leading to postnatal cerebellar dysfunction and epilepsy, have never been reported before. Presented case may contribute to the broadening of the spectrum of sparse prenatal features of JRSD, and support the stand that presence of neuronal migration abnormalities can affect the clinical outcome and prognosis of fetuses with JSRD.